Ritual Semah di Desa Kuala Tolam Kabupaten Pelalawan Provinsi Riau: Analisis Teori Mircea Eliade - Ali, Muhammad Harfi; Hakim, Lukmanul (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The Semah ritual is a cultural tradition of the people of Kuala Tolam Village, Pelalawan Regency, which functions as a means of treatment for the sick and a way to overcome problems related to spirits with the aim of protecting the village. This ritual combines spiritual, social and cultural aspects that are passed down from generation to generation. This article aims to analyse the Semah Ritual using Mircea Eliade's sacredness and profanity theory approach, which highlights the role of ritual symbols in creating a connection between humans and the sacred dimension. Using qualitative methods and Mircea Eliade's approach, this research explores the experiences of local people in undergoing rituals as an integral part of their lives. The results show that the Semah Ritual is not just a customary tradition, but also has a deep meaning as a means of bringing the community closer to the transcendent. The symbols used in the ritual, such as offerings, mantras, and dance movements, reflect the harmonious relationship between humans, nature, and spiritual entities. This ritual serves as a medium to strengthen local cultural identity while overcoming life's challenges, both physical and metaphysical. In addition, the implementation of the Semah Ritual is also a space for social interaction that strengthens community solidarity. This article emphasises the importance of understanding cultural practices such as the Semah Ritual in the context of maintaining the sustainability of local traditions and building deeper spiritual connections. Thus, the Semah Ritual is not only a cultural expression, but also a reflection of the dynamics of the relationship between humans, nature and the divine in the daily lives of the Kuala Tolam Village community.